2022
DOI: 10.3390/membranes12020184
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of a Cell Culture Medium Treated with a High-Voltage Pulse Using Stainless Steel Electrodes and the Role of Iron Ions

Abstract: High-voltage pulses applied to a cell suspension cause not only cell membrane permeabilization, but a variety of electrolysis reactions to also occur at the electrode–solution interfaces. Here, the cytotoxicity of a culture medium treated by a single electric pulse and the role of the iron ions in this cytotoxicity were studied in vitro. The experiments were carried out on mouse hepatoma MH-22A, rat glioma C6, and Chinese hamster ovary cells. The cell culture medium treated with a high-voltage pulse was highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Temperature of the textile‐based electrofluidic platform was also monitored to identify whether there was an impact of temperature rise on cell viability. Joule heating causes electrolyte evaporation during electrophoretic applications [34]. As shown in supporting information Figure S3, after 1 h, the temperature and current of different voltages stabilised at 32.5–33.4°C and 7.8–20.8 µA, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature of the textile‐based electrofluidic platform was also monitored to identify whether there was an impact of temperature rise on cell viability. Joule heating causes electrolyte evaporation during electrophoretic applications [34]. As shown in supporting information Figure S3, after 1 h, the temperature and current of different voltages stabilised at 32.5–33.4°C and 7.8–20.8 µA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The electric field is considered to affect the electrochemical potential across the cell membrane and cause instabilities in the polarised cell membrane lipid bilayer. Higher electric fields have been applied to cells in electric field involved cell culture applications [34][35][36]. Electroporation is often employed in medicine and biotechnology to transfer nonpermeable chemical species through the cell membrane [35].…”
Section: Investigation Of Cell Viability With Textile-based Electrofl...mentioning
confidence: 99%
“…These parameters include sampled molecules abundance in the cell, their diffusivity in the extracellular fluid and water, transport through the cell membrane, transport through the extracellular space from the cells to the harvesting needle, and transport to the e-biopsy syringe [ 54 ]. In addition, previous studies showed the indirect effect of pulsed electric fields on tissue, such as changing the environment pH [ 55 ], catalyzing multiple electrochemical reactions [ 56 ], and releasing metals from the electrodes [ 57 ], all of which could affect the sampled tissue volume and affect the sampled proteome quality. Elucidating these properties for the potential biomarkers for tumors is required for the construction of robust models of molecular transport from cells to the e-biopsy syringe.…”
Section: Resultsmentioning
confidence: 99%
“… 102 Compared to bare platinum electrodes, stimulation with stainless-steel electrodes is reported to be more cytotoxic. 103 In most studies, one or both electrodes were positioned within the muscle, which is to limit damage to the spinal cord itself. 53,69,71,73,74,78,81,84,104 …”
Section: Electrode Materialsmentioning
confidence: 99%